2018
DOI: 10.1155/2018/2802803
|View full text |Cite
|
Sign up to set email alerts
|

Criterion-Related Validity of a Simple Muscle Strength Test to Assess Whole Body Muscle Strength in Chinese Children Aged 10 to 12 Years

Abstract: Objective To study the criterion-related validity of simple muscle strength test (SMST) indicators and assess whole body muscle strength in Chinese children aged 10 to 12 years old. Methods Two hundred and forty children were equally divided into four groups in different genders and residences. The SMST indicators (hand-grip, knee bent push-up, back muscle strength, sit-up, leg muscle strength, and standing long jump) were tested. We set up the total level of the whole-body muscle strength (Ftotal) through tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
2
6
0
2
Order By: Relevance
“…We report similar grip strength in urban and rural samples, as did one prior study of urban and rural 10–12 year old Chinese children [ 46 ]. One puzzling observation is that grip strength was somewhat higher in urban compared to rural mothers despite more time spent farming and in household activities.…”
Section: Discussionsupporting
confidence: 82%
“…We report similar grip strength in urban and rural samples, as did one prior study of urban and rural 10–12 year old Chinese children [ 46 ]. One puzzling observation is that grip strength was somewhat higher in urban compared to rural mothers despite more time spent farming and in household activities.…”
Section: Discussionsupporting
confidence: 82%
“…Although a few validation studies have been conducted for SBJ, the difference in population in term of age, gender, experience require a new study of the relevant population (Yin, Tang, & Tao, 2018;Reid, Dolan, & De Beliso, 2017;Fernandez-Santos, Ruiz, Cohen, Gonzalez-Montesinos, & Castro-Pinero, 2015). Besides, the process of validation and reliability is about obtaining and gathering the evidence to support the score interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…The summarized available evidence showed that the FSM (4-10 years), BOUGE health-related fitness battery (8-16 years), fitness test battery (3-6 years), and test battery (5-12 years) are reliable measures to use in children with TD. The construct of the FSM, test battery, fitness test battery, and simple muscle strength test 79 were shown to be valid in children with TD. So far, only the upper limb section of the FSM, specifically for measuring muscle power, has been recommended by Bieber et al (2016); however, this recommendation was based on only 2 identified studies of children with DCD.…”
Section: Muscle Powermentioning
confidence: 95%